The complex within-person relationship between individual creative expression and subsequent creative process engagement. Issue 6 (1st November 2020) - Li, Ci-Rong; Yang, Yanyu; Lin, Chen-Ju; Liu, Jing
ABSTRACT: In the present research, we examine the competing predictions of achievement motivation theory and self-regulation theories (i.e., social cognitive theory and the control view) regarding the within-person relationship between individual creative expression and subsequent creative process engagement (CPE). Furthermore, we investigate creative self-efficacy as a mediator of this complex relationship and hypothesize that a state regulatory focus helps explain when individual creative expression curvilinearly relates to subsequent CPE. We undertook two studies to investigate our hypotheses. First, we conducted a weekly field study with 201 technicians over five measurement occasions. The results showed that the within-person relationship between individual creative expression and subsequent CPE is curvilinear and revealed that creative self-efficacy belief mediates this curvilinear relationship. Second, we conducted a weekly study over 5 weeks with 120 R&D workers and also found a curvilinear relationship between individual creative expression and subsequent CPE (mediated by creative self-efficacy belief) at the within-person level. The results also revealed that the positive relationship was weakened and the negative relationship was strengthened when the promotion focus state was higher; the curvilinear relationship then emerges in a weaker prevention focus state. These findings improve our understanding of how and when individual creative expression influences subsequent CPE.